2021
DOI: 10.1177/09544100211007386
|View full text |Cite
|
Sign up to set email alerts
|

Study on the aerodynamic performance of boundary-layer-ingesting inlet with various geometries

Abstract: The mixing loss in S-shaped duct causes the contradiction between the total pressure recovery and circumferential distortion, which confuses the design process for boundary layer ingestion (BLI) inlet. This article is aiming to present a detailed understanding of the effect of two kinds of loss resources (mixing loss and frictional loss) on the performance for various BLI inlet geometries. To achieve the above objective, a design method including three control parameters is established. With this method, a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Rein and Koch 48 demonstrated that the distortion at the AIP increases proportionally with the thickness of the inlet boundary layer. Thick boundary layers were found to reduce also the pressure recovery on the intake [49][50][51] and to promote non-uniform radial pressure loading on the compressor blades which could trigger stall inception. 4 Different azimuthal orientations of the approaching boundary layer were also investigated for intakes under yaw and pitch angles 52,53,18 were found to notably influence the fan-face pressure and swirl distortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rein and Koch 48 demonstrated that the distortion at the AIP increases proportionally with the thickness of the inlet boundary layer. Thick boundary layers were found to reduce also the pressure recovery on the intake [49][50][51] and to promote non-uniform radial pressure loading on the compressor blades which could trigger stall inception. 4 Different azimuthal orientations of the approaching boundary layer were also investigated for intakes under yaw and pitch angles 52,53,18 were found to notably influence the fan-face pressure and swirl distortion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the associated peak distortion levels were not assessed as a part of these previous studies and most studies were limited to investigations on the time-averaged components. 50 The understanding of peak distortion levels is a key aspect for the evaluation of the engine response to the inlet distortion. Indeed, it is believed that peak fluctuations of pressure, vorticity and velocity can all play a role in the spike-type stall inception mechanism, which is a source of instability for modern, highly loaded compressors.…”
Section: Introductionmentioning
confidence: 99%